A phase II basket trial of Dual Anti–CTLA–4 and Anti–PD–1 Blockade in Rare Tumors (DART) SWOG S1609: High‐grade neuroendocrine neoplasm cohort. Issue 17 (21st April 2021) - Patel, Sandip Pravin; Mayerson, Edward; Chae, Young Kwang; Strosberg, Jonathan; Wang, Jue; Konda, Bhavana; Hayward, Jourdain; McLeod, Christine M.; Chen, Helen X.; Sharon, Elad; Othus, Megan; Ryan, Christopher W.; et al.
Abstract : Background: The authors previously reported the results of the nonpancreatic neuroendocrine neoplasm cohort of the SWOG S1609 DART (Dual Anti–CTLA‐4 and Anti–PD‐1 Blockade in Rare Tumors) trial, which permitted all histologic grades and had a 44% overall response rate (ORR) among patients with high‐grade disease. Here they sought to validate their findings in a dedicated prospective cohort of high‐grade neuroendocrine neoplasms within S1609. Methods: A prospective, open‐label, multicenter, phase 2 clinical trial of ipilimumab plus nivolumab was conducted across multiple rare tumor cohorts. The dedicated, high‐grade neuroendocrine neoplasm cohort was examined here. The primary end point was the ORR according to version 1.1 of the Response Evaluation Criteria in Solid Tumors. Secondary end points included progression‐free survival (PFS), overall survival (OS), and toxicity. Results: Nineteen patients with high‐grade neuroendocrine neoplasms (defined by local pathology review) were enrolled in this cohort of S1609. The most common primary sites were unknown primaries (21%), which were followed by the rectum, gastroesophageal junction, cervix, and pancreas (11%). The median number of lines of prior therapy was 1 (range, 0‐3). All patients were microsatellite‐stable. The median Ki‐67 value was 80%. The ORR was 26% (95% confidence interval [CI], 11%‐45%), and the clinical benefit rate (stable disease for ≥6 months plus partial responses plus complete responses) was 32% (95% CI, 13%‐57%). The 6‐month PFS rate was 32% (95% CI, 16%‐61%) with a median PFS of 2.0 months (95% CI, 1.8 months to ∞) and a median OS of 8.7 months (95% CI, 6.1 months to ∞). The most common toxicities were fatigue (32%) and rash (26%), and the most common grade 3/4 immune‐related adverse event was rash (15%); there were no events that required treatment discontinuation and no grade 5 events. Conclusions: Ipilimumab plus nivolumab demonstrated a 26% ORR in patients with high‐grade neuroendocrine neoplasms, with durable responses seen in patients with refractory disease. Abstract : Low‐dose ipilimumab with nivolumab results in a 26% overall response rate in high‐grade neuroendocrine neoplasms.